2019
DOI: 10.1111/jcmm.14235
|View full text |Cite
|
Sign up to set email alerts
|

MARCH1 encourages tumour progression of hepatocellular carcinoma via regulation of PI3K‐AKT‐β‐catenin pathways

Abstract: Membrane‐associated RING‐CH‐1 (MARCH1) is a membrane‐anchored E3 ubiquitin ligase that is involved in a variety of cellular processes. MARCH1 was aberrantly expressed as a tumour promoter in ovarian cancer, but the signalling about the molecular mechanism has not yet been fully illuminated. Here, we first determined that MARCH1 was obviously highly expressed in human hepatocellular carcinoma samples and cells. In addition, our findings demonstrated that the proliferation, migration and invasion of hepatocellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…Also, several reports showed that the PI3K pathway might be related to tumorigenesis and tumor development [9,20]. According to the clinical research, p-AKT was higher in the tumor (53%) than in cirrhotic tissues (12%) while it was absent from normal liver [21]. PI3K/Akt signaling pathway is also confirmed to be associated with poor survival, high tumor grade, intrahepatic metastasis, as well as vascular invasion in HCC patients.…”
Section: Discussionmentioning
confidence: 96%
“…Also, several reports showed that the PI3K pathway might be related to tumorigenesis and tumor development [9,20]. According to the clinical research, p-AKT was higher in the tumor (53%) than in cirrhotic tissues (12%) while it was absent from normal liver [21]. PI3K/Akt signaling pathway is also confirmed to be associated with poor survival, high tumor grade, intrahepatic metastasis, as well as vascular invasion in HCC patients.…”
Section: Discussionmentioning
confidence: 96%
“…For examples, expression of MARCH1 is up-regulated following TNFα, IL-1β, and TGFβ stimulation (54). The transcription of MARCH1 gene is induced by IL-10 and LPS in monocytes or DCs, while its expression is decreased during maturation of DCs, indicating that MARCH1 plays important roles in regulating antigen presentation and DC maturation (22, 25, 31, 33, 34, 55). The transcription of MARCH9 gene is increased in human DCs upon Toll-like receptor (TLR) 3 or 4 activation (22).…”
Section: Properties Of the March E3 Ligase Family Membersmentioning
confidence: 99%
“…The transcription of MARCH3 gene is dramatically induced by LPS and TLR8 agonist in monocytes (56). Notably, it has been demonstrated that MARCH1 is highly expressed in human hepatocellular carcinoma (HCC) cells (55), MARCH5 is up-regulated in ovarian cancer tissues (28), and MARCH8 is highly expressed in esophageal tumors and associated with tumor aggression (50). These studies suggest that certain MARCH proteins may involve in tumorigenesis.…”
Section: Properties Of the March E3 Ligase Family Membersmentioning
confidence: 99%
“…It suggests that multi-omics analysis, including epigenetic data, could improve availability of output, in terms of precision medicine or personalized medicine, as we recently reported [65]. The E3 ubiquitin ligase MARCH1 plays an important role in immunology [66], although only a few publications have focused on MARCH1 in the context of cancer [67,68]. Therefore, further studies in this area are required and could have the potential to contribute to the field of cancer research, and more particularly lung cancer.…”
Section: Discussionmentioning
confidence: 89%